2023
DOI: 10.17219/dmp/147754
|View full text |Cite
|
Sign up to set email alerts
|

Oral health-related quality of life and xerostomia in type 2 diabetic patients

Abstract: Background. Diabetes mellitus (DM) is a known risk factor for xerostomia. Oral health-related quality of life (OHRQoL) is a multi-dimensional issue reflecting several effects of the oral condition on the quality of life.Objectives. The present study aimed to assess OHRQoL and its relationship with xerostomia severity in type 2 diabetic patients. Material and methods.A total of 200 patients participated in this cross-sectional study. The Xerostomia Inventory (XI) assessed xerostomia severity and the Oral Health… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 21 publications
0
0
0
Order By: Relevance
“…In contrast, systemic disorders such as thyroid diseases and diabetes appear to have a comparatively minor effect on OHRQoL. Our findings suggest a seemingly positive impact of diabetes on OHRQoL, a result that diverges from the findings of several other studies 4,31–34 …”
Section: Discussioncontrasting
confidence: 99%
See 1 more Smart Citation
“…In contrast, systemic disorders such as thyroid diseases and diabetes appear to have a comparatively minor effect on OHRQoL. Our findings suggest a seemingly positive impact of diabetes on OHRQoL, a result that diverges from the findings of several other studies 4,31–34 …”
Section: Discussioncontrasting
confidence: 99%
“…Our findings suggest a seemingly positive impact of diabetes on OHRQoL, a result that diverges from the findings of several other studies. 4,[31][32][33][34] This unexpected finding prompts further investigation and potential explanations. One plausible interpretation lies in the gender distribution within our study cohort, where men constituted the majority of participants (54%).…”
Section: Discussionmentioning
confidence: 78%
“…Similar findings were presented by Larsen et al but in a higher percentage [32]. Xerostomia can be related to general medication and general disease, among others, as highlighted in a recent manuscript describing oral health-related quality of life and xerostomia in type 2 diabetic patients [33]. The authors confirmed that wearing dentures, age, the duration of disease, and the medical management of diabetes mellitus also correlated significantly with oral health-related quality of life questionnaire answers provided by patients for this purpose.…”
Section: Discussionsupporting
confidence: 85%